EVALUATION OF STUDENTS' CREATIVE THINKING SKILLS IN WRITING FANTASY TEXTS IN JUNIOR HIGH SCHOOL GRADE VII - Pangestuti, Peni (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to assess students' creative thinking skills in writing fantasy texts in grade VII. Creative thinking is an important skill to create students' unique and innovative ideas. Fantasy text as the object of research because it provides freedom of exploration of imagination and ideas beyond the limits of reality, so it can measure students' creativity. The method used in this research is descriptive qualitative. Data were collected through document analysis of the results of fantasy text writing of seventh grade students. The assessment instrument applied refers to the indicators of creative thinking ability which includes fluency in generating many ideas, flexibility in generating various ideas, originality in creating unique ideas, and elaboration in describing ideas in detail. The research findings show that the creative thinking ability of seventh grade students in writing fantasy texts needs to be improved. The fluency and elaboration aspects are satisfactory, but the flexibility and originality aspects are still low. This shows that students tend to produce the same ideas and are less innovative. The implication of this study is the importance of developing writing learning strategies that focus more on stimulating the flexibility and originality aspects of creative thinking.